Children and global conflict - Huynh, Kim, 1977-; D'Costa, Bina.; Lee-Koo, Katrina (2015)
"Over one billion people under the age of eighteen live in territories affected by armed conflict. Despite this, scholars and practitioners often lack a comprehensive knowledge of how children both struggle within and shape conflict zones. Children and Global Conflict provides this understanding with a view to enhancing the prospects of conflict resolution and peacebuilding. This book presents key ideas and issues relating to children's experiences of war, international relations and international law. The authors explore the political, conceptual and moral debates around children in these contexts and offer examples and solutions based on case studies of child soldiers from Vietnam, child forced migrants in Australia, young peace-builders in post-conflict zones, youth in the international justice system, and child advocates across South Asia and the Middle East"--
"This book presents key ideas and issues relating to children's experiences of war, international relations and international law. The authors explore the political, conceptual and moral debates around children in these contexts and offer examples and solutions based on case studies of child soldiers from Vietnam, child forced migrants in Australia, young peace-builders in post-conflict zones, youth in the international justice system, and child advocates across South Asia and the Middle East"--
Introduction: Why children matter to global conflict -- 1. Children and armed conflict : mapping the terrain -- Introduction -- The social construction of childhood -- The construction of contemporary conflict zones -- The experiences of children affected by armed conflict -- Conclusion -- 2. Children and agency : caretakers, free-rangers and everyday life -- Introduction -- Caretakers: why children should be neither seen nor heard -- Free-rangers: why children are autonomous -- Children and practice of everyday life -- Conclusion -- 3. Children and IR : creating spaces for children -- Introduction -- The realist way of conflict -- The liberal peace -- The new wars -- Critical approaches to IR theory -- Conclusion -- 4. The rights of the child : political history, practices and protection -- Introduction -- Children's rights across cultural contexts -- A history of children's rights: laying the moral foundations -- Discursive practices of rights along the global north and south divide -- The UNCRC -- International law and the protection of children in armed conflict -- Child civilians -- 'An era of application' and the UN resolutions -- Conclusion -- 5. Child soldiers : causes, solutions and cultures -- Introduction -- The problem of child soldiers: the caretaker position -- The problem of child soldiers: the free-ranger position -- An indirect approach to the problem of child soldiers -- Child soldier cultures -- Vietnam's child soldiers: fathers, giants and emperors -- Vietnam's child soldiers: total war, new heroes and martyrs -- Conclusion -- 6. Child forced migrants : bio-politics, autonomy and ambivalence -- Introduction -- The age of forced migration -- Children and the age of forced migration -- The view from down under: nonhuman children -- The view from down under: re-humanising children -- Ambivalent conclusions -- 7. Children and peace building : propagating peace -- Introduction -- Searching for children in international peace building -- The youth bulge thesis -- Children and everyday peace -- Conclusion -- 8. Children and justice : past crimes, healing and the future -- Introduction -- The evolution of juvenile justice systems -- The child in international criminal justice -- Truth and healing through restorative justice -- Conclusion -- 9. Who speaks for children? : advocacy, activism and resistance -- Introduction -- Civil society -- The transformative politics of advocacy: naming and shaming -- The transformative politics if advocacy: CZOP -- Children as activists -- Children as political subjects - babies as political objects -- Conclusion -- Conclusion.
Includes bibliographical references (pages 287-319) and index.
Keywords: Children and war; Children and politics; Children -- Government policy; Child soldiers; Child soldiers; Children and politics; Children and war; Children -- Government policy; Kinderen; Gewapende conflicten; Barn och krig